Super‐Hydrated Zeolites: Pressure‐Induced Hydration in Natrolites. Issue 33 (12th July 2013) - Seoung, Donghoon; Lee, Yongmoon; Kao, Chi‐Chang; Vogt, Thomas; Lee, Yongjae
Abstract High‐pressure synchrotron X‐ray powder diffraction studies of a series of alkali‐metal‐exchanged natrolites, A16Al16Si24O80⋅n H2O (A=Li, K, Na, Rb, and Cs and n=14, 16, 22, 24, 32), in the presence of water, reveal structural changes that far exceed what can be achieved by varying temperature and chemical composition. The degree of volume expansion caused by pressure‐induced hydration (PIH) is inversely proportional to the non‐framework cation radius. The expansion of the unit‐cell volume through PIH is as large as 20.6 % in Li‐natrolite at 1.0 GPa and decreases to 6.7, 3.8, and 0.3 % in Na‐, K‐, and Rb‐natrolites, respectively. On the other hand, the onset pressure of PIH appears to increase with non‐framework cation radius up to 2.0 GPa in Rb‐natrolite. In Cs‐natrolite, no PIH is observed but a new phase forms at 0.3 GPa with a 4.8 % contracted unit cell and different cation–water configuration in the pores. In K‐natrolite, the elliptical channel undergoes a unique overturn upon the formation of super‐hydrated natrolite K16Al16Si24O80⋅32 H2O at 1.0 GPa, a species that reverts back above 2.5 GPa as the potassium ions interchange their locations with those of water and migrate from the hinge to the center of the pores. Super‐hydrated zeolites are new materials that offer numerous opportunities to expand and modify known chemical and physical properties by reversibly changing the composition and structure using pressure in the presence of water.